2013
DOI: 10.1099/ijs.0.046128-0
|View full text |Cite
|
Sign up to set email alerts
|

Phaeobacter leonis sp. nov., an alphaproteobacterium from Mediterranean Sea sediments

Abstract: A novel Gram-stain-negative, strictly aerobic, heterotrophic bacterium, designated 306 T , was isolated from near-surface (109 cm below the sea floor) sediments of the Gulf of Lions, in the Mediterranean Sea. Strain 306 T grew at temperatures between 4 and 32 6C (optimum 17-22 6C), from pH 6.5 to 9.0 (optimum 8.0-9.0) and between 0.5 and 6.0 % (w/v) NaCl (optimum 2.0 %). Its DNA G+C content was 58.8 mol%. On the basis of 16S rRNA gene sequence similarity, the novel isolate belongs to the class Alphaproteobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Recently, Phaeobacter strains retrieved a lot of interest because of their production of various secondary metabolites (e.g., Berger et al, 2011). Analyses of the 16S rRNA gene and in some publications also preliminary genomic analyses were in conflict with the current classification (Jin et al, 2011; Beyersmann et al, 2013; Buddruhs et al, 2013a; Dogs et al, 2013a,b; Freese et al, 2013; Gaboyer et al, 2013; Riedel et al, 2013; Breider et al, 2014; Liu et al, 2014; Park et al, 2014). These analyses mostly showed that P. aquaemixtae, P. caeruleus, P. daeponensis, Leisingera methylohalodivorans , and L. aquimarina form a clade, P. arcticus and P. leonis comprise a distinct monophyletic group, and P. gallaeciensis and P. inhibens form a third clade.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Phaeobacter strains retrieved a lot of interest because of their production of various secondary metabolites (e.g., Berger et al, 2011). Analyses of the 16S rRNA gene and in some publications also preliminary genomic analyses were in conflict with the current classification (Jin et al, 2011; Beyersmann et al, 2013; Buddruhs et al, 2013a; Dogs et al, 2013a,b; Freese et al, 2013; Gaboyer et al, 2013; Riedel et al, 2013; Breider et al, 2014; Liu et al, 2014; Park et al, 2014). These analyses mostly showed that P. aquaemixtae, P. caeruleus, P. daeponensis, Leisingera methylohalodivorans , and L. aquimarina form a clade, P. arcticus and P. leonis comprise a distinct monophyletic group, and P. gallaeciensis and P. inhibens form a third clade.…”
Section: Introductionmentioning
confidence: 97%
“…The genus Phaeobacter was introduced by Martens et al (2006) and currently comprises the species Phaeobacter aquaemixtae (Park et al, 2014), Phaeobacter arcticus (Zhang et al, 2008), Phaeobacter caeruleus (Vandecandelaere et al, 2009), Phaeobacter daeponensis (Yoon et al, 2007), Phaeobacter inhibens (Martens et al, 2006), Phaeobacter leonis (Gaboyer et al, 2013), and Phaeobacter gallaeciensis (Ruiz-Ponte et al, 1998; Martens et al, 2006), which is the type species, its type strain being BS107 T = CIP 105210 T = DSM 26640 T but not DSM 17395 (Buddruhs et al, 2013b). The Phaeobacter species were isolated from a mixing zone of the ocean and a freshwater spring, marine arctic sediment, a marine electro-active biofilm, tidal flat sediment, a tidal mud flat, marine surface sediment and rearings and collectors of the scallop Pecten maximus , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Phaeobacter, currently comprising the species Phaeobacter gallaeciensis, P. inhibens, P. daeponensis, P. caeruleus, P. arcticus and P. leonis (Gaboyer et al, 2013), belongs to the marine Roseobacter clade. It was established by Martens et al (2006) after reclassification of Roseobacter gallaeciensis (Ruiz-Ponte et al, 1998) as P. gallaeciensis, which is the type species of the genus, and description of P. inhibens as a new species.…”
Section: Introductionmentioning
confidence: 99%
“…Among them is that of Phaeobacter inhibens DSM 17395 (12), which was recently reclassified from Phaeobacter gallaeciensis DSM 17395 (13). Phaeobacter species are globally distributed in the marine system, e.g., in sediments of the Arctic Ocean (14), the Yellow Sea (15), and the Mediterranean Sea (16), and in surface water of the German Wadden Sea (17). Furthermore, they are constituents of marine biofilms (18) and are associated with scallops (19) and algae (12).…”
mentioning
confidence: 99%